THE HYPOTHESIS OF “THE ESCAPE FROM THE MALTHUSIAN TRAP” THROUGH THE “FASTER TECHNOLOGICAL GROWTH”: THE CRITICAL ANALYSIS - A. A. Romanchuk (Концепт: философия, религия, культура, 2019)
The key thesis of cliodynamics is a conclusion that starting from the certain moment of human history the technologies began to grow faster than the growth of population of the planet. The followers of the hypothesis suppose that this allowed the humans “to escape” from “the Malthusian trap”, i.e. the regularly overpopulation crises that led traditional societies to collapses. However, the critical analysis draws a more complicated picture. First, we can suppose that many (at least, many) of traditional societies achieved the limits of their social and political durability earlier than the resource limits. Secondly, from the very beginning of human history there were known some deliberate mechanisms of lowering of population growth, such as infanticide and regulated cannibalism. Thirdly, by no means denying that the technological growth increases the medium bearing capacity, we can suppose that the free space reserves was a very important factor of the Earth population achieved at the mid of XX century. That is why the thesis of “the technological growth faster than the population growth” looks controversially. Finally, even the modern societies “escaped” from the “Malthusian trap” through the decreasing of population growth, using the mechanism of fertility decline.